La certificación de comercio justo como factor clave en las negociaciones de las empresas exportadoras. - Arciniega Guzman, Jair Enrique (My University, 2021)
Exporting companies are facing the dynamism of international markets, highlighting the change in consumer preferences, now more focused on the valuation of social aspects. The Fair Trade model certification is a strategic alternative that companies around the world have adopted to cover the needs of a growing market niche, willing to pay a higher price for the promise of contributing to the sustainability of producers and agricultural workers. The purpose of this research is to identify the variables in which the Fair Trade strategy is promoted, within the framework of the organizational practices applied by exporting companies in the agricultural sector of several countries. The study was carried out under a qualitative approach, based on the systematization and analysis of 15 scientific articles, selected using specific criteria associated with the research objective. Among the main results, it stands out that exporting companies have prioritized the variables: wages, investment of premiums based on prices, social responsibility, organizational culture, communication with the consumer. It is concluded that the organizational practices of companies reflect adaptations of infrastructure, agricultural processes, and processes to strengthen the empowerment of workers.
Las empresas exportadoras se enfrentan al dinamismo de los mercados internacionales, destacándose el cambio en las preferencias de los consumidores, ahora más enfocados en la valoración de aspectos sociales. La certificación del modelo de Comercio Justo es una alternativa estratégica que han adoptado las empresas alrededor del mundo para dar cobertura a las necesidades de un nicho de mercado en crecimiento, dispuesto a pagar un precio más alto por la promesa de contribuir a la sostenibilidad de productores y trabajadores agrícolas. El propósito de esta investigación es identificar las variables en las que se impulsa la estrategia de Comercio Justo, en el marco de las prácticas organizacionales aplicadas por empresas exportadoras del sector agropecuario de varios países. El estudio se realizó bajo un enfoque cualitativo, a partir de la sistematización y análisis de 15 artículos científicos, seleccionados mediante criterios específicos asociados al objetivo de investigación. Entre los principales resultados se destaca que las empresas exportadoras han priorizado las variables: salarios, la inversión de las primas a partir de los precios, responsabilidad social, cultura organizacional, comunicación con el consumidor. Se concluye que las prácticas organizacionales de las empresas reflejan adaptaciones de infraestructura, procesos agrícolas, procesos para fortalecer el empoderamiento de los trabajadores.
Keywords: EXPORTACIONES; PRÁCTICAS ORGANIZACIONALES